Exponential Predefined Time Trajectory Tracking Control for Fixed-Wing UAV With Input Saturation - Zhao, Shulong; Zheng, Jiayi; Yi, Feng; Wang, Xiangke; Zuo, Zongyu (IEEE transactions on aerospace and electronic systems, 2024)
This article proposes a spatio-temporal trajectory tracking protocol for a fixed-wing unmanned aerial vehicle (UAV) subject to unknown disturbances and input saturation, using the exponential predefined time control (EPTC). First, aiming at the problem that the control magnitude may grow violently while approaching the predefined time, we introduce an exponential controller to compensate for the predefined time controller. Then, fixed time disturbance observers (FTDOs) are designed to estimate the unknown external disturbances and unmodeled terms of the fixed-wing UAV. The nonlinear input saturation is linearized by a Gaussian error function and addressed by auxiliary variables. Through rigorous analysis, we prove that FTDOs will converge within a fixed time and that tracking errors are bounded within this period. In the presence of input saturation, the tracking errors can converge to zero within a predefined time, irrespective of the initial states. The results of numerical simulations demonstrate that the proposed protocol can guarantee the convergence of the tracking errors within a predefined time. That is, the EPTC protocol has a spatio-temporal characterization. The change in the control magnitude is moderate compared with the existing works, which is more suitable for the fixed-wing UAV. Moreover, the flight test realizes the extension on a real fixed-wing UAV and verifies the practical feasibility of the proposed spatio-temporal trajectory tracking protocol.